Increasing Throughput Potential in Functional-Oriented Machining Plants - Lewestam, Adam; Mäki, Henrik (My University, 2015)
Productivity and throughput are central aspects in a production system´s ability to satisfy market demand. Throughput is thus an indicator of system performance and is dependent on how the production resources are utilized. Machining plants, for which a functional oriented production layout is given, are exposed to a number of factors limiting their maneuverability when striving to increase throughput and better satisfy their customers. Based on this, the purpose of this thesis is to investigate capacity losses, analyze the potential for increasing throughput and propose an approach for how to fulfill this potential. To fulfill this purpose, the thesis is based on a case study at a Swedish company in the Aerospace industry that finds itself in this situation. The research strategy is a combination of both quantitative and qualitative methods in terms of production data analysis, interviews and observations. The analysis revealed that the case company's production system loses 28 % of its available capacity with its current set-up and planning and control procedures. This capacity loss is mainly caused by two factors. The first one, high variability, negatively impacts the lead time at any given utilization level and creates a disrupted product flow. The second one, high levels of Work-In-Process, leads to unnecessary bottlenecks, long lead times and an inertly production system. High variability and Work-In-Process are in turn effects of a number of identified physical and managerial constraints that must be elevated in order to increase throughput. The thesis results in a recommended framework that aims at increasing throughput for functional-oriented machining plants, without major investments or physical rearrangements. The framework combines new layout and routing principles with the use of simpler planning and control procedures, which primarily will reduce variations, complexity, unnecessary Work-In-Process and lead times. This creates a pulling product flow that is more predictable and transparent. The new principles are in turn supported by an aligned business governance and performance measurement strategy, matching the current manufacturing situation.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics